Ra'yu Di Kalangan Madzhab Empat: Studi Terhadap Frekuensi Pengggunaan Ra'yu Dalam Bab Talak: The Use of Reasoning (Ra'yu) in the Four Sunni Madhhabs: A Study of Its Frequency in the Jurisprudence of Divorce (Ṭalāq) - Abdul Haris (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2002)
A widespread assumption among Muslims holds that the Hanafi school uses personal opinion (ra’yu) most frequently, followed by the Shafi’i and Maliki schools, while the Hanbali school uses it least. This study re-examines this hierarchy by analyzing the use of ra’yu through jurisprudential reasoning methods (bayani, qiyasi/ta'lili, and istishlahi), not merely the quantity of hadith. The research aims to measure the actual proportion of ra’yu usage across the four schools, specifically regarding divorce (talak). Using library research and comparative and historical analysis, this study scrutinizes key issues: explicit divorce terms, contextual indications (qarinah), divorce by an intoxicated or coerced person, and the status of a woman during a minor irrevocable divorce waiting period. The findings reveal a different order: the Hanbali school demonstrates the highest engagement with ra’yu, followed by the Maliki, then the Hanafi, with the Shafi’i school using it most sparingly in divorce rulings. The study concludes that the mainstream perception is empirically unsupported and recommends re-evaluating the classification of schools as